What patients want to know before they have cataract surgery. Issue 3 (20th February 2004) - Elder, M J; Suter, A
Abstract : Aims: To investigate what patients want to know before undergoing cataract surgery. Methods: A written questionnaire was answered by 190 patients prior to cataract surgery. Results: The five pieces of preoperative information rated most important were: chance of visual improvement; when vision would improve; overall risk of losing vision from the operation; effect of not having the operation, and the types of serious complications. When asked "should you be warned of a serious complication if it has a risk of happening", 93.5% said yes to a risk of 1 in 50 and 62.4% to 1 in 1000. Written information was requested by 85.7%. There were few differences between the sexes, and between those having their first or second operation. Conclusions: Patients most wanted to know benefits and risks, even very small risks. Written information should be provided to ensure coverage and reinforce verbal information.